Infrastructure Planning: Intermediary of Indonesia’s Community Health in Climate Change Era (A Bibliometric Analysis) - Rose Fatmadewi (UPT Publikasi Ilmiah UNISBA, 2025)
Climate change has impacts on a broad spectrum of challenges, including social, economic, and environmental problems. The impacts of climate change on human health include increases in respiratory, vector-borne, and zoonotic diseases. The research focuses on one aspect of supporting human health that is often ignored in the climate change adaptation process: infrastructure planning. This article discusses this problem through a review of various research/literature which is grouped thematically with case studies in Indonesia. Based on a thematic discussion, it was found that the research that had been carried out still lacks on spatial studies of infrastructure planning’s discussion, especially those related to health-supporting infrastructure in the climate change era. These findings can ultimately provide a lot of input on research themes related to the importance of infrastructure planning as an intermediary towards a healthy and resilient society against climate change.